NUMERICAL AND PARAMETRIC STUDY ON THE GEOPOLYMER CONCRETE CORE IN COMPOSITE SANDWICH SECTION - THOOY, KOK YAW (Universiti Teknologi PETRONAS, 2020)
Conventional Ordinary Portland Concrete (OPC) based concrete is one of the widely used material in construction field that involved in the development of country. OPC concrete is a double-edged sword due to the resulting environmental issue caused by its manufacturing process. It can be minimized and its durability can be enhanced by replacing it with alternative solution such as composite sandwich section with geopolymer concrete core that made up by the combination of steel plates and geopolymer concrete that connected by shear connectors. The conventional OPC concrete is weak in resisting high temperature and acid environment. The non-covered OPC concrete is exposed directly to the environment where a sudden impact on the structure might break or crack the surface that reduce the strength of the concrete structure.